Aero engine compressor fouling effects for short- and long-haul missions - Igie, Uyioghosa; Goiricelaya, Mike; Nalianda, Devaiah (Sage, 2015)
The impact of compressor fouling on civil aero engines unlike the industrial stationary application has not been widely investigated or available in open literature. There are questions about the impact of fouling for short- and long-haul missions comparatively, given their unique operational requirements and market. The aim of this study is to quantify the effects of different levels of fouling degradation on the fan, for two different aircraft with different two-spool engine models for their respective typical missions. Firstly, the study shows the increase in turbine entry temperature for both aircraft engines, to maintain the same level of thrust as their clean condition. The highest penalty observed is during take-off and climb, when the thrust setting is the highest. Despite take-off and climb segment being a larger proportion in the short-haul mission compared to the long-haul mission, the percentage increase in fuel burn due to fouling are similar, except in the worst case fouling level were the former is higher by 0.8% points. In addition to this, for all the cases, the additional fuel burn due to fouling and its cost is shown to be small. Likewise, the increase in turbine entry temperature for both missions at take-off are similar, except in the worst case fouling level for the short-haul mission were the turbine entry temperature is 7 K higher than the corresponding long-haul mission for the same level of degradation. The study infers that the penalty due to rise in temperature is of more concern than the additional fuel burn. Hence the blade technology (cooling and material) and engine thrust rating are key factors in determining the extent to which blade fouling would affect aero engine performance in short- and long-haul missions.
Keywords: Jet engine model; aero engine operation; compressor fouling; short-haul; long-haul